Naringine Extrait d’agrumes comme inhibiteurs de corrosion de l’acier au carbone dans un milieu d’acide chlorhydrique a différent pH - Boukhezna, Samiha; Gadi, Ibtissame; Ghribi, Zineb (université d'eloued, 2023)
"The calculation of corrosion thickness on the surface of a carbon steel provides insight into the development of this phenomenon and the degradation of the material over time, which can lead to disruptions in industrial production chains. The first part of this study involved a theoretical explanation of the electrochemical techniques used to determine the corrosion thickness of an iron oxide film through the reaction between protons in water, where hydrochloric acid with a concentration of 0.5 M is dissolved, and the metal cation Fe2+. The objective of this study was to investigate the corrosion inhibition power of an Naturel compound, namely Naringin, using the equivalent circuit model. This model helped us determine the thickness of the iron oxide film formed in the absence and presence of different inhibitor concentrations, with immersion times of up to 120 minutes. The obtained results indicate that the inhibitory power increases with Naringin concentration, reaching maximum effectiveness at around 30 ppm. The Tafel plot results indicate that Naringin exhibits cathodic inhibition, as evidenced by the shift of the corrosion potential towards negative values, with a displacement of -250 mV. In summary, this study provided a comprehensive understanding of corrosion thickness and corrosion inhibition in carbon steel. The results highlight the efficacy of the naturel compound Naringin as a corrosion inhibitor, with an optimal concentration of approximately 30 ppm. Furthermore, the Tafel plot analysis reveals cathodic inhibition properties. These findings can contribute to the development of corrosion protection strategies in industries where carbon steel is widely utilized. " "حساب سمك التآكل على سطح فولاذ الكربون يوفر فكرة عن تطور هذه الظاهرة وتدهور المادة مع مرور الوقت، مما يمكن أن يؤدي إلى انقطاع في سلاسل إنتاج الصناعة. تم في الجزء الأول من هذه الدراسة شرح نظري مفصل للتقنيات الكهروكيميائية المستخدمة لتحديد سمك التآكل لطبقة أكسيد الحديد من خلال تفاعل بروتونات الماء، حيث يتم ذلك بذوبان حمض الهيدروكلوريك بتركيز 0.5 مول/لتر وكاتيون المعدن الحديد Fe2+. هدف هذه الدراسة هو دراسة قدرة مثبط التآكل لمركب طبيعي، وهو مركب النارينجين، باستخدام نموذج الدائرة المكافئة. ساعدنا هذا النموذج في تحديد سمك طبقة أكسيد الحديد المتكونة في الغياب وفي وجود تراكيز مختلفة من المثبط، بوقت غمر يصل إلى 120 دقيقة. أشارت النتائج المحصل عليها إلى أن قدرة مثبط التآكل تزداد مع تركيز النارينجين، وتصل إلى أقصى فاعلية عند تركيز حوالي 30 جزء في المليون. أما نتائج قياسات تافيل، فتشير إلى أن النارينجين لديه تثبيط من النوع الكاثودي، حيث يتحرك جهد التآكل نحو القيم السالبة، مع انحراف بمقدار -250 ملي فولت. في الخلاصة، قدمت هذه الدراسة فهمًا شاملاً لسمك التآكل وتثبيط التآكل في فولاذ الكربون. تسلط النتائج الضوء على فعالية المركب الطبيعي النارينجين كمثبط للتآكل، مع تركيز أمثل حوالي 30 جزء في المليون. بالإضافة إلى ذلك، تكشف تحليلات قياسات تافيل عن وجود تثبيط كاثودي. يمكن أن تساهم هذه النتائج في تطوير استراتيجيات الحماية من التآكل في الصناعات التي يستخدم فيها فولاذ الكربون بشكل واسع "
مذكرة ماستر هندسة كيميائيةDes thèses génie chimique
Keywords: Corrosion, Electrochemical impedance spectrum, polarization curve.; التآكل ، طيف الممانعة الكهروكيميائية ، منحنى الاستقطاب.